Um estudo sobre construções dos Números Reais - Queiroz, Fabiana Moura de (2015)
The main objective of this paper is to present the subtle passage of rational numbers to the real numbers, using a construction via Dedekind cuts and other by Cauchy sequences .We present a construction of rational numbers by equivalence classes, so that the reader has a foundation that serves as a support for a good understanding of proposed constructions of real numbers . We use the axiomatic method for buildings that are made on real numbers, in order to show the existence of an orderly and complete field and characterize it. It is also discussed, and a more synthesized form, the real numbers and its application to elementary and high school students.